Land-use change influence ecosystem services in an agricultural landscape in Central America - Tobar López, Diego E.; Muriel, Bonin; Andrade, Hernán J.; Ibrahim, Muhammad (2022)
Ecosystems provide a variety of services that are important for human well-being. The estimation of different ecosystem services is necessary to support decision-making processes at different levels in the landscapes. The dynamics of land use, based on LANDSAT satellite images from the years 1978, 1986, 1998 and 2011 in La Vía Láctea (Nicaragua), was analyzed to estimate its impact on four ecosystem services (habitat for species, carbon stock, greenhouse gas regulation and food production). The valuation of ecosystem services was carried out through a land-use change analysis, while the estimation of conservation value coefficients was estimated for the study area using information collected in the field. It was estimated that forest cover was reduced by 93% between 1978 and 2011, whereas pasture areas increased considerably (133,304 ha) in the same period. These changes have caused a reduction of forest cover for cattle production, resulting in a loss in the quality and provision of ecosystem services. The conversion of forests to pastures caused a reduction of ecosystem services such as habitat for species and carbon stock, while milk production and greenhouse gas emissions have increased, which is related to grassland management. Between 1978 and 2011, support and regulation services had decreased by $15.6 and $4.4 million USD, respectively, whereas provisioning services have increased by $14.9 million USD. Recovery of pastures through silvopastoral systems is an alternative that would improve the provision of ecosystem services and the promotion of sustainable livestock to improve landscape conservation.